2021
DOI: 10.3390/polym13244465
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Conducting Flexible Thin Films of Composites from Poly(ethylene oxide) and Nematic Liquid Crystals E8—Characterization by Impedance and Dielectric Relaxation Spectroscopy

Abstract: Complex electrical impedance and dielectric spectroscopy were applied to study the dielectric relaxations and their thermal behavior in ion-conducting composites/complexes from polymer poly(ethylene oxide) (PEO) and E8 nematic liquid crystals (LCs), at the compositional ratio PEO:E8 = 70:30 wt%. Flexible thin films of PEO/E8 with a thickness of 150 μm were inspected, as well as such films from Na+ ion-conducting electrolyte PEO/E8/NaIO4 with the same PEO:E8 compositional ratio, but additionally containing 10 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 83 publications
2
21
0
Order By: Relevance
“…The oscillating electric field can cause the dipoles in such complex dielectric material to align, resulting in polarization. As recently reported, this can be evidenced by analyses of the thermodynamical behaviors of the PNLCCs …”
Section: Key Characteristics Of Ion-conducting Pnlccssupporting
confidence: 64%
See 3 more Smart Citations
“…The oscillating electric field can cause the dipoles in such complex dielectric material to align, resulting in polarization. As recently reported, this can be evidenced by analyses of the thermodynamical behaviors of the PNLCCs …”
Section: Key Characteristics Of Ion-conducting Pnlccssupporting
confidence: 64%
“…For such ion-conducting PNLCCs where metal ions are active for the ion transport, the same conclusions from impedance studies may be drawn, regarding the presence of molecular dipoles, dipole polarization (dipolar reorganization), and dipole relaxation (dielectric relaxation of dipoles) driven by an external AC electric field. Significantly, in this case the value of f max Z″ is higher, and the characteristic dielectric relaxation time is shorter, as compared to the corresponding undoped (base) ion-conducting PNLCCs (Figure b and c) . This is explained with the structural changes induced by the ion donor, mainly the increase of the amorphous portion in the PNLCC material and, thereby, the increase in the segmental motion of polymer chains due to the addition of the salt. , …”
Section: Key Characteristics Of Ion-conducting Pnlccsmentioning
confidence: 79%
See 2 more Smart Citations
“…In addition, it has been reported that 5CB can greatly improve the e r of a polymer matrix such as PMMA, 31 PS 32 and PEO. 33 Moreover, the average dielectric constant of 5CB in the liquid crystal state is 10.8, 34 and the dielectric constant is 10.5 when the temperature is above 40 1C. 35 As a consequence, the dielectric constant difference between 5CB and PVDF (e r is around 8) is small, thus avoiding the large local electric field difference between the components.…”
Section: Introductionmentioning
confidence: 99%